Clinical and epidemiological characteristics of HIV. Luis Augusto Turcios Lima University Polyclinic - Ramírez Guzmán, Sandra; Capote Serrano, Rigoberto (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
A descriptive and transversal research was carried out with the purpose of characterizing clinical and epidemiological aspects in HIV patients at the Turcios Lima polyclinic from June 2020 to June 2022. The universe consisted of 64 patients with HIV and the sample coincided with this universe. A questionnaire was applied to each patient where variables such as sex, age, race, marital status, education level, occupation, age of diagnosis of the disease, toxic habits, time of evolution of the disease, most frequent symptoms, psychosocial characteristics of the family, degree of family functioning, risk factors, CD4 lymphocyte count at diagnosis, treatment and whether or not adherence to treatment were collected. To obtain the information, a questionnaire and instruments such as the FFSIL test for the perception of family functioning and the Morinsky-Green-Levine Self-Reported Compliance Test to measure adherence to treatment will be applied. Among the main results it was found that most of the patients were between 40 and 49 years of age, male, with a schooling level of 12th grade, with the age of diagnosis being 30 years, predominance of smoking as a toxic habit, good psychosocial characteristics, and a high level of adherence.